Football and the media construction of Iranian national identity during the FIFA World Cup 2018 and AFC Asian Cup 2019 - Ziaee, A.; Adib-Moghaddam, A.; Elling, A.; van Sterkenburg, J.; van Hilvoorde, I. (Soccer & Society, 2021)
Elite sport success in international tournaments is supposed to play an important role in shaping national identity. In this article, we explore if and how this applies to the Iranian context. The current study made use of a Google alert with the title of `Iran Men`s National Football Team`, and a general content analysis of Iranian national and sport media. The analytic focus was on media coverage of the Iranian national football team at the 2018 FIFA World Cup and the 2019 AFC Asian Cup. All relevant newspaper articles before, during, and after Iran`s matches were reviewed, coded, and analysed. We developed four main themes in the coverage expressing Iranian identity in the context of the aforesaid football events: `united passion`, `determined and conscientious`, `oppressed but great`, and `emotion-ridden`. It was concluded that political and historical references used by Iranian media contribute to the invention and reproduction of Iranian national identity through the aforementioned sporting tournaments.